2020
DOI: 10.1111/jvim.15858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient content and caloric density in commercially available foods formulated for senior cats

Abstract: Background: Cat foods marketed for senior cats (≥7 years) are available to owners. The variability in the nutritional content of these foods is unknown. Objectives: To measure the caloric density and caloric distribution of crude protein, crude fiber, crude fat, phosphorus, calcium, magnesium, sodium, potassium, and vitamin D3 in commercially available foods for senior cats and to compare nutrient content with foods for adult cats. Samples: Thirty-one senior and 59 adult commercial nontherapeutic cat food prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this study, Ca/P ratio ranged from 0.91 to 1.1 in dog food, while in cat food, it was slightly higher, ranging from 1.13 to 1.98. Also, our general Ca/P ratio (1.33±0.25) for pet food for adult cats was similar to those reported in study by Summers et al (2020) in cat foods labeled for senior and adult cats (1.3 and 0.8-1.7, respectively). The Ca/P ratios in pet food for dogs (0.91-1.51) were in accordance, in general, with the recommended (AAFCO, 2018) guidelines, in which a minimum Ca/P ratio of 1:1 and a maximum ratio of 2:1 are advised.…”
Section: Resultssupporting
confidence: 89%
“…In this study, Ca/P ratio ranged from 0.91 to 1.1 in dog food, while in cat food, it was slightly higher, ranging from 1.13 to 1.98. Also, our general Ca/P ratio (1.33±0.25) for pet food for adult cats was similar to those reported in study by Summers et al (2020) in cat foods labeled for senior and adult cats (1.3 and 0.8-1.7, respectively). The Ca/P ratios in pet food for dogs (0.91-1.51) were in accordance, in general, with the recommended (AAFCO, 2018) guidelines, in which a minimum Ca/P ratio of 1:1 and a maximum ratio of 2:1 are advised.…”
Section: Resultssupporting
confidence: 89%
“…18,19 While there is no maximum dietary Ca:P recommendation for cats, most diets tend to stay below 2.0:1. 20,21 It has recently been demonstrated that feeding a lowphosphate diet to cats with CKD increases the risk for the development of hypercalcemia. 4,5,12,13 Conversely, many studies have demonstrated the utility of feeding a reduced-phosphate diet in slowing the progression of CKD and decreasing the markers of CKD mineral and bone disorders.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 While there is no maximum dietary Ca:P recommendation for cats, most diets tend to stay below 2.0:1. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…The Cu, Fe and Zn data for this study were from a food analysis performed in two previously published studies that evaluated calcium and phosphorus content in commercial adult and senior cat foods. 19,20 Cat foods were categorized based on the marketing terms for specific life stages on the label’s principle display and on the intended use based on being formulated or feeding trialed for specific life stages as indicated by the label’s nutritional adequacy statement. Food (dry, canned and raw) marketed for adult and senior cats were purchased from grocery and pet stores in the Fort Collins, CO, USA area.…”
Section: Methodsmentioning
confidence: 99%